A, E-Business & E-Commerce. B&C E-Business & E-Commerce: The structure of the new commerce world and how Ghanaians are seriously equipping themselves and poised to be included in this modern and global business transaction: There are 2 other articles submitted - Kwadade-Cudjoe, Francis (Archives of Business Research, 2020)
E-Business and E-Commerce are currently the vogue in transacting business globally. The mode of transacting business with this modern approach is so simple that, it is likely a huge number of the global population are already there. Ghana, an emerging market in Africa and the globe, has the attractiveness to join this craze. The current government has been able to eliminate the quack financial institutions from the banking system, and technologically established and launched the infrastructure for Ghana’s Interbank Payment and Settlement Systems (GhIPSS). This is an internet payment gateway to enable holders of domestic Automated Teller Machine (ATM) cards to make payments and purchases online. Most of the Banks in Ghana have also come out with perks to customers who would adopt the online purchasing approach, and even use their ATM cards for their transactions. The enticement is seriously catching on, and there is the hope that the citizenry would listen to the advice of the government for all to join the digital transformation currently going on in Ghana.